An exploration of the correlations between seven psychiatric disorders and the risks of breast cancer, breast benign tumors and breast inflammatory diseases: Mendelian randomization analyses - Ren, Fei; Shang, Qingyao; Zhao, Shuangtao; Yang, Chenxuan; Feng, Kexin; Liu, Jiaxiang; Kang, Xiyu; Zhang, Ruixuan; Wang, Xiang; Wang, Xin (Frontiers in Psychiatry, 2023)
Previous observational studies have showed that certain psychiatric disorders may be linked to breast cancer risk, there is, however, little understanding of relationships between mental disorders and a variety of breast diseases. This study aims to investigate if mental disorders influence the risks of overall breast cancer, the two subtypes of breast cancer (ER+ and ER-), breast benign tumors and breast inflammatory diseases. During our research, genome-wide association study data for seven psychiatric disorders (schizophrenia, major depressive disorder, bipolar disorder, post-traumatic stress disorder, panic disorder, obsessive-compulsive disorder and anorexia nervosa) from the Psychiatric Genomics Consortium and the UK Biobank were selected, and single-nucleotide polymorphisms (SNPs) significantly linked to these mental disorders were identified as instrumental variables. GWAS data for breast diseases came from the Breast Cancer Association Consortium as well as the FinnGen consortium. We performed two-sample Mendelian randomization analyses and multivariate MR analyses to assess these SNPs' effects on various breast diseases. Both heterogeneity and pleiotropy were evaluated by sensitivity analyses. When the GWAS data of psychiatric disorders were derived from the PGC, our research found that schizophrenia significantly increased the risks of overall breast cancer (two-sample MR: OR 1.05, 95%CI [1.03-1.07], P = 3.84×10-6; multivariable MR: OR 1.06, 95%CI [1.04-1.09], P = 2.34×10-6), ER+ (OR 1.05, 95%CI [1.02-1.07], P = 5.94×10-5) and ER- (two-sample MR: OR 1.04, 95%CI [1.01-1.07], P = 0.006; multivariable MR: OR 1.06, 95%CI [1.02-1.10], P = 0.001) breast cancer. Nevertheless, major depressive disorder only showed significant positive associations with overall breast cancer (OR 1.12, 95%CI [1.04-1.20], P = 0.003) according to the two-sample MR analysis, but not in the multivariate MR analyses. In regards to the remainder of the mental illnesses and breast diseases, there were no significant correlations. While as for the data from the UK Biobank, schizophrenia did not significantly increase the risk of breast cancer. The correlations between schizophrenia and breast cancer found in this study may be false positive results caused by underlying horizontal pleiotropy, rather than true cause-and-effect relationships. More prospective studies are still needed to be carried out regarding the definitive links between mental illnesses and breast diseases.